Histopathological Analogies in Chronic Pulmonary Lesions between Cattle and Humans: Basis for an Alternative Animal Model - Ramírez Romero, Rafael; Nevárez Garza, Alicia Magdalena; Rodríguez Tovar, Luis Edgar.; Wong González, Alfredo; Ledezma Torres, Rogelio Alejandro; Hernández Vidal, Gustavo (Hindawi Publishing Coorporation, 2012)
Most of the natural cases of pneumonia in feedlot cattle are characterized by a longer clinical course due to chronic lung lesions. Microscopically, these lesions include interstitial fibroplasia, bronchitis, bronchiectasis, bronchiolitis obliterans, and epithelial metaplasia of the airways. Herein, the aim was to review, under a medical perspective, the pathologic mechanisms operating in these chronic pneumonic lesions in calves. Based on the similarities of these changes to those reported in bronchiolitis obliterans/organising pneumonia (BO/OP) and chronic obstructive pulmonary disease (COPD) in human beings, calves are proposed as an alternative animal model.